Less invasive monitoring of cougars in Colorado's front range. (5th July 2019) - Alldredge, Mat W.; Blecha, Tasha; Lewis, Jonathan H.
ABSTRACT: From 2014 to 2016, in the Front Range of Colorado, USA, we assessed noninvasive approaches to sampling cougar ( Puma concolor ) populations in an attempt to provide a new method that would be less field intensive, less expensive, and could be applied over large spatial extents compared with current methods. We assessed the use of predator calls to lure cougars to a site with remote camera traps for detection and also evaluated hair snags at sites to noninvasively identify individual animals. Predator calls effectively attracted cougars to specific sites with an average of 82 unique photographic detections of cougars per survey year (0.03 detections/trap‐night). However, obtaining hair samples from these animals was less effective because animals did not always pass through hair snags and ability to uniquely identify individuals by genotype was poor. We evaluated different approaches to estimating cougar density and found mark–resight to be a viable option in our study system. Mark–resight density estimate after correcting for partial use of the sampling area by cougars was 4.1 cougars/100 km 2 (95% CI = 2.4, 5.8). Our results indicate that combining methods of noninvasive genetic sampling and auditory calls to monitor cougar populations can provide reliable density estimates over large geographic areas and areas with significant amounts of inaccessible private lands. © 2019 The Wildlife Society. Abstract : Currently Colorado, USA, does not have any current estimates of cougar population density, so this study was conducted to develop reliable techniques to sample cougar populations and produce a reliable density estimate. We found, using predator calls and trail cameras in a mark‐resight framework, cougar density was 4.1 cougars/100 km 2 in a lightly hunted cougar population in the Front Range of Colorado.